THE IMPORTANCE AND UTILIZATION OF BIG DATA FOR INDONESIAN MARITIME INFORMATION - Zainul Hidayah (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Sea ​​transportation mode is still the favourite in the business world because of its high carrying capacity (capacity) and more competitive costs compared to other modes of transportation. As a country that has a vast marine area, Indonesia certainly has many problems related to its marine area. Indonesia faces various potential trans-national crimes that usually occur at sea such as illegal fishing, smuggling of goods, drugs and human, terrorism and piracy. Based on the complex conditions of the potential problems that arise in the maritime sector, all stakeholders and law enforcement officers at sea need integrated maritime information management to support their duties in maintaining security in Indonesia's waters. Therefore, it is hoped that the use big data of maritime information will be able to help stake holders involved in overcoming these problems. Keywords : big data analysis, sea transportation, maritime information; Indonesian water